Brands and consumers : a research overview - Singh, Jaywant; Crisafulli, Benedetta (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"Brand management is firmly established as a core business and marketing activity. The research evidence on how consumers react to branding, however, is in constant evolution globally. This shortform book provides a comprehensive overview of research evidence on several core branding topics whilst acting as a catalyst for advancing future research and informing business practice. The book fills a gap created by prior volumes on branding that, although well-illustrated and explained, have approached the subject in somewhat uncritical manner. As such, the book represents a timely compendium on popular topics in branding and is a valuable addition to knowledge in branding. The book focuses on reviewing research in branding and brand management, and delves into proposing areas for expanding knowledge in the field. Recognising the diversity of research in branding, the authors of this book as active branding researchers attempt to discuss the limitations of current research and provide insights for future explorations. The book will be of interest and a valuable resource for academic researchers, branding practitioners, business students and policy makers who view branding as an evidence-oriented discipline"--
Keywords: Branding (Marketing) -- Management; Marketing research; BUSINESS & ECONOMICS / Marketing / General